Novel synthesis, optical, and photoluminescence properties of Mg x Zn1-x O nanoflowers - Aal, Nadia Abdel; Al-Ghamdi, Ahmed A.; Al-Hazmi, Faten; Fathia, Shokr; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Springer, 2015)
Novel flower-like hierarchical nanostructures consisting of Mg (x) Zn1-x O semiconductors were successfully synthesized by the hydrothermal technique. X-ray diffraction results indicate that the Mg (x) Zn1-x O (x = 0-0.25 at %) samples are single hexagonal phase. The grain morphology and spatial compositions of Mg (x) Zn1-x O nanoflowers were systematically observed by field-emission scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray analysis. The UV-Visible absorption spectra show that the band gap of Mg (x) Zn1-x O nanoflowers can be readily tuned by optimizing the molar ratio of Mg precursors. The photoluminescence line shapes of the Mg (x) Zn1-x O samples of Mg composition ranging from 0 up to 0.25 at % were found to exhibit the inherent doping broadening, which masks the excitonic emissions. These nanostructures may be used for various optoelectronic nanodevices owing to its low cost and easy scaling up.
Keywords: MgxZn1-xO alloy nanoflowers; Hydrothermal synthesis; Nanostructures; Optical properties